The Effect of Empowerment, Work Environment and Career Development on Employee Performance with Work Motivation as an Intervening Variable in the Government of Aceh - Indonesia - Em Yusuf Iis; Wahyuddin Wahyuddin; Armanu Thoyib; Rico Nur Ilham; Irada Sinta (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of employee empowerment, work environment, and career development on the performance of Aceh Government employees. Data was obtained by distributing questionnaires to 150 employees. The data analysis method is Structural Equation Modeling (SEM). The results showed that employee empowerment, work environment, and employee career development had a significant effect on work motivation and employee performance. In addition, employee empowerment and work motivation have a direct and significant effect on employee performance, and career development and work environment also have a direct effect on performance. Work motivation partially mediates the effect of employee empowerment, work environment, career development on performance. The Aceh Government is expected to improve career development in order to create a conducive work environment to improve the performance of Aceh Government employees.